Atmospheric pressure non‐equilibrium plasma cleaning of 19th century daguerreotypes. Issue 3 (29th September 2016) - Boselli, Marco; Chiavari, Cristina; Colombo, Vittorio; Gherardi, Matteo; Martini, Carla; Rotundo, Fabio
Abstract : In the work, the feasibility of using atmospheric pressure non‐equilibrium plasmas to clean the surface of a deteriorated 19th century daguerreotype has been examined and a proof‐of‐principle demonstration is given. The daguerreotype was treated by means of both a commercial plasma jet source (kINPen 09, Neoplas Tools GmbH) and a specially designed Dielectric Barrier Discharge (DBD) plasma source operated within a controlled volume at atmospheric pressure, by using a argon‐hydrogen gas mixture (H2 content: 35% vol.) to remove corrosion products, without immersion of the substrate in solvents or chemicals. The effectiveness of plasma treatment in removing tarnishing products while preventing damage to the fragile image has been evaluated analysing the surface by means of scanning electron microscopy (SEM) with energy dispersive microprobe (EDS) for localized elemental analysis, micro‐Raman and ATR‐FTIR spectroscopy for phase identification. Abstract : Two different atmospheric pressure non‐thermal plasmas have been used to clean the surface of a corroded 19th century daguerreotype. The influence of the plasma treatment on the image quality, surface composition and its effectiveness in removing tarnishing products has been evaluated by means SEM with EDS for localized elemental analysis, micro‐Raman and ATR‐FTIR spectroscopy for phase identification.